MEMAHAMI LIBERALISASI PERDAGANGAN: DAMPAK DAN IMPLIKASINYA DALAM KONTEKS EKONOMI GLOBAL - Wafik Azizah; Binar Nan Baik (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Trade liberalization is the process of reducing trade barriers between countries, such as tariffs and quotas, with the aim of increasing the flow of goods and services globally. This paper examines the impact and implications of trade liberalization in the global economy, both in terms of advantages and disadvantages. On the one hand, liberalization can improve industrial efficiency, expand market access, and encourage economic growth, especially in developing countries. However, on the other hand, trade liberalization can also cause losses for certain sectors, such as local industries that cannot compete with cheaper imported products. This study uses a descriptive qualitative research method, presenting data naturally and in accordance with field conditions. Through this approach, data is processed and analyzed to describe the reality of the phenomenon being studied. In addition, this study is also strengthened by a theoretical basis and literature review to support the research. The main findings show that the impact of trade liberalization is highly dependent on the readiness of policies and economic structures of each country. Developing countries need to adopt policies to protect vulnerable sectors, such as subsidies or workforce training, to maximize the benefits of liberalization. In addition, the role of international trade organizations such as the WTO is also important in overseeing and regulating global trade, despite facing challenges in ensuring compliance and equality between member countries.